THE CONTENT OF GAMES AND THEIR ROLE IN THE DEVELOPMENT OF COMMUNICATIVE COMPETENCES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
The article examines the pedagogical potential of communicative games in teaching English to primary school learners. Special attention is paid to the role of the teacher’s professional authority and positive emotional attitudes in shaping learners’ communicative culture and social behavior. The study argues that game-based activities, predominantly cooperative in nature, create favorable conditions for developing spontaneous speech, dialogic interaction, and non-aggressive communication skills.The paper analyzes the structure and components of educational games, including goal setting, planning, role distribution, symbolic use of objects, and result evaluation. A distinction is made between communicative and linguistic games, highlighting their objectives, content, and learning outcomes. It is emphasized that communicative games prioritize meaningful interaction and task completion over formal linguistic accuracy.